Isolation of Cellulolytic Fungi from Municipal Garbage and Screening for their Cellulase Activity, Saccharification and Protein Production (Bangladesh Journal of Genetics and Biotechnology, 2009)
Key words: Municipal garbage; Isolation; Screening; Cellulase Bangladesh j. genet. biotechnol. 7(1&2): 49-52 2006 (June & December)